The Practice and Politics of Reading, 650-1500 - Donoghue, Daniel, 1956-; Simpson, James; Watson, Nicholas; Wilson, Anna B.; Appleford, Amy, 1970-; De Groot, Michelle; Johnston, Andrew James; Kraebel, A. B. (Andrew Brock), 1983-; O'Brien O'Keeffe, Katherine, 1948-; Sanok, Catherine; Seal, Samantha Katz; Simpson, James, 1954-; et al. (Boydell & Brewer, Limited, 2022)
A new look at how reading was practised and represented in England from the seventh century to the beginnings of the print era, finding many kinships between reading cultures across the medieval longue durée.